A comparison between overweight cutoff points for detection of high blood pressure in adolescents - Christofaro, Diego G. D.; Fernandes, Romulo A. [UNESP]; Polito, Marcos D.; Romanzini, Marcelo; Vaz Ronque, Enio Ricardo; Gobbo, Luis Alberto; de Oliveira, Arli Ramos (Sociedade Brasileira de Pediatria, 2009)
Objectives: To evaluate the accuracy of three different cutoff points for the detection of high blood pressure in adolescents, given the strong relationship between overweight and high blood pressure levels.Methods: A total of 1,021 adolescents of both sexes were enrolled in the study, selected at random from public and private schools in Londrina, Brazil. Their body weight was measured using a digital balance, and their height with a portable stadiometer with a maximum extension of 2 meters. Arterial blood pressure was measured using an automatic apparatus. The capacity of body mass index to detect high blood pressure was gauged using ROC curves and their parameters (sensitivity, specificity, and area under the curve).Results: The cutoff points proposed in a Brazilian standard exhibited greater accuracy (males: 0.636 +/- 0.038; females: 0.585 +/- 0.043) than the cutoff points proposed in an international (males: 0.594 +/- 0.040; females: 0.570 +/- 0.044) and a North-American standard (males: 0.612 +/- 0.039; females: 0.578 +/- 0.044).Conclusions: The Brazilian proposal offered greatest accuracy for indicating high blood pressure levels.
Comparação entre pontos de corte para excesso de peso na detecção de pressão arterial elevada em adolescentes